SAS Essentials Mastering SAS for Data Analytics - Elliott, Alan C. (John Wiley & Sons, Incorporated, 2015)
reference for researchers and academicians who require a basic introduction to SAS for statistical analysis and for preparation for the Basic SAS Certification Exam.
Description based on publisher supplied metadata and other sources
Keywords: Datenverarbeitung; Analysis of variance -- Computer programs; Mathematical statistics -- Data processing; SAS (Computer file); SAS -- Programm